Medical decision making - Sox, Harold C.; Higgins, Michael C. (Michael Clark), 1950-; Owens, Douglas K.; Sanders Schmidler, Gillian; Ohio Library and Information Network (Hoboken, NJ : John Wiley & Sons, Inc., 2024)
"This volume addresses these needs. Chapters 1 and 2 set the stage: uncertainty is everywhere in clinical practice, yet clinical reasoning depends on logical deduction as exemplified by differential diagnosis. Chapters 3, 4, and 5 are about defining and navigating uncertainty: determining probability, updating probability, and the determinants of post-test probability, all basic tools of the clinician. Chapters 6 and 7 are about modeling the factors that shape decisions. Chapters 8-12 explore in-depth the measurement of utility, both the basics and the underlying theory. Topics include attitudes toward taking risks, the quality of life, and the length of life. The last three chapters are about making decisions: deciding when to treat, when to test, and when to wait (Chapter 13); the advanced modeling methods that inform policy. (Chapter 14); and cost-effectiveness analysis (Chapter 15)"--
Differential Diagnosis -- Probability : Quantifying Uncertainty -- Interpreting New Information : Bayes' Theorem -- Measuring The Accuracy Of Clinical Findings -- Decision Trees : Representing The Structure Of A Decision Problem -- Decision Tree Analysis -- Outcome Utility : Representing Risk Attitudes -- Outcome Utilities : Clinical Applications -- Outcome Utilities : Adjusting For The Quality Of Life -- Survival Models : Representing Uncertainty About The Length Of Life -- Markov Models : Structure -- Selection And Interpretation Of Diagnostic Tests -- Medical Decision Analysis In Practice : Advanced Methods -- Cost-Effectiveness Analysis
Includes bibliographical references and index
Keywords: Clinical medicine -- Decision making; Diagnosis -- Decision making; Diagnosis, Differential; Decision making; Decision making -- Mathematical models; Probabilities; Cost effectiveness; Decision Making; Probability; Cost-Benefit Analysis; Clinical Decision-Making.; Diagnosis, Differential; Decision Support Techniques